Impact of Running Speed and Limb Muscle Strength on Squat Style Long Jump for Secondary School - Galih Yoki Haryanto; Hartati Hartati; Ahmad Richard Victorian (Journal of Innovation in Educational and Cultural Research, 2023)
This study aims to determine the impact of running speed and limb muscle strength on the squat-style long jump results of State Senior High School students. The participants of this study were 40 people. The data collection technique for measuring speed was the 40-meter sprint test, for measuring limb muscle strength, namely the standing broad jump test, and for measuring the long jump style squat, namely the long jump style squat test. Data analysis techniques to find out the relationship between (X1, Y) and (X2, Y) used the Product Moment Correlation Formula. The Linearity Test was intended to test whether the data obtained is linear or not. If the data is linear, then it can be continued with the regression technique. The finding concludes that the three variables have a significant value that is less than 0.05 (significant value 0.05). The multiple correlations (R) between the independent variable and the dependent variable have a significant relationship because of F-count (18.5) â‰¤ F-table (37). This means that there is a contribution to the relationship between running speed and limb muscle strength with the results of the squat-style long jump. So, schools can take advantage of the results of this research as one of the considerations for providing facilities for long jump activities and providing teaching materials for sports teachers.